Private Rescue Echo Beacon with FSK Radiomodule - Moshenskyi, Andrii (My University, 2020)
Rescue personnel work in high-risk environments. As a result of injuries, the problem of evacuating the lifeguard from the facility may arise. GPS navigation is not available in restricted areas, for example, in rooms, basements. Rational use of radio responders for direction finding of the object. A radio direct finding complex is not always convenient and can be quickly deployed, for example, in a basement in case of fire. It is more convenient to use the blind bearing method with existing VHF radio stations. Professional radio stations usually do not have an indicator of signal strength, and have limited controls such as volume, channel selection, and PTT. It is proposed to use a carrier transponder at a given frequency based on SI44XX with stepwise adjustable power and synchronously changing audio filling tone in FSK or GFSK mode.
Keywords: beacon; VHF (UHF); FSK; MCU; power; tone; маяк; УКХ; ЧМ; МК; потужність; тон; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки